Development of Student E-Attendance System using QR-Code and WhatsApp Gateway with The Iterative Model Based on Android - Mar’atuttahirah; Miftahulkhairah; Alfito, Ramadan Barik (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
The rapid advancement of technology not only creates new industries but also reshapes global competition. In higher education, learning implementation must meet standards for content, process, and assessment. Student attendance plays a significant role within these standards. Using Android smartphones for attendance tracking resolves issues related to student presence, saves time, and enhances the efficiency and accuracy of the attendance recapitulation process for lecturers. This study explores an innovative system that integrates QR-Code and WhatsApp Gateway using an iterative model on a single platform. Blackbox testing confirmed that all features and functions of the Android application work as intended. Furthermore, a Likert scale evaluation scored 89%, indicating that the e-attendance system effectively facilitates student attendance and helps lecturers summarize attendance data more accurately and efficiently. The system then provides this data as administrative monitoring reports for the academic department regarding the conducted lectures.